Pengaruh E-Service Quality terhadap E-Customer Loyalty melalui E-Customer Satisfaction sebagai Variabel Intervening Pada Aplikasi Tiket.com - Tri Atmojo, Jose Juang; Widodo, Teguh (Jurnal Manajemen, 2022)
Online travel agency business sector shows a contradiction that even though e-service quality is still a lot of complaints, it has no effect on e-customer satisfaction. This study aims to analyze the direct effect of E-Service Quality on e-customer loyalty directly or through E-Customer Satisfaction as an intervening variables of Tiket.com application. A total of 259 respondents who have used the Tiket.com application were taken as samples with a non-probability sampling method, namely purposive sampling. Respondents were asked to provide their perceptions on five ordinal scales of 25 statement items. All indicators belonging to each variable have been tested for validity and reliability. Before testing the hypothesis, the fit model is tested with the eligibility criteria. Four that are interrelated to form a hypothetical equation model (SEM) are tested for significance by the T test and then the strength of their influence is measured. All calculations for testing are carried out with LISREL 8.8 software. The results of this study indicate that E-Service Quality has.a positive and significant effect.on E-Customer.Satisfaction.. E-customer satisfaction has a positive and significant effect on e-customer loyalty. E-service quality has not directly affect on E-Customer Loyalty. E-service quality has a positive and significant indirect effect on e-customer loyalty through E-Customer.Satisfaction. The most influential dimension of E-Service Quality is User Friendly. This study recommends an effective way to increase loyalty to the online travel agency industry and strengthens the research model on e-loyalty based on e-service quality.